Ukraine in the Information and Communication Technology Development Ranking. II - Tutova, O.V.; Savchenko, Ye.A. (Управляющие системы и машины, 2019)
The paper considers the level and evolution of information and communication technology developments in Ukraine and its experience relative to other Eastern European and post-Soviet countries based on the Information and Communication Technology Development Index over 2002-2017. Also modeling of the indicators characterising the development of information and telecommunication technologies in Ukraine is presented.